Gravitationally decoupled charged anisotropic solutions in Rastall gravity - Sadiq, Sobia; Waseem, Arfa; Javed, Faisal; Errehymy, Abdelghani; Abdel-Aty, Abdel-Haleem (Frontiers in Astronomy and Space Sciences, 2024)
This paper develops the stellar interior geometry for charged anisotropic spherical matter distribution by developing an exact solution of the field equations of the Rastall gravity using the notion of gravitational decoupling. The main purpose of this investigation yields the extension of the isotropic well-known model within the context of charged isotropic Rastall gravity solutions. The second aim of this work is to apply the gravitational decoupling via a minimal geometric deformation scheme in Rastall gravity. Finally, the third one is to derive an anisotropic version of the charged isotropic model previously obtained by applying gravitational decoupling technology. We construct the field equations which are divided into two sets by employing the geometric deformation in radial metric function. The first set corresponds to the seed (charged isotropic) source while the other one relates deformation function with an extra source. We choose a known isotropic solution for spherical matter configuration including electromagnetic effects and extend it to an anisotropic model by finding the solution of the field equations associated with new source. We construct two anisotropic models by adopting some physical constraints on the additional source. To evaluate the unknown constants, we use the matching of interior and exterior spacetimes. We investigate the physical feasibility of the constructed charged anisotropic solutions by the graphical analysis of metric functions, density, pressure, anisotropy parameter, energy conditions, stability criterion, mass function, compactness and redshift parameters. For the considered choice of parameters, it is concluded that the developed solutions are physically acceptable as all the physical aspects are well-behaved.